2013
DOI: 10.1111/jth.12103
|View full text |Cite
|
Sign up to set email alerts
|

Is a decrease of microparticles related to improvement of hemostasis after FVIII injection in hemophilia A patients treated on demand?

Abstract: Blood samples were taken before and 30 min after FVIII injection in 18 patients with severe hemophilia A treated on demand. Flow-cytometric determination of total MPs (TMPs) using lactadherin, platelet MPs (PMPs) (CD42a), endothelial MPs (EMPs) (CD144) and leukocyte MPs (LMPs) (CD45) was performed. The results were compared with data on endogenous thrombin potential (ETP), overall hemostatic potential (OHP), fibrin gel permeability and thrombin-activatable fibrinolysis inhibitor (TAFI). Results and Conclusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
(36 reference statements)
4
5
0
Order By: Relevance
“…We also observed a lower number of CD62+ MVs in patients, both in the baseline sample and after the infusion of FVIII in comparison to the controls. Our patients showed a lower amount of CD144+ microvesicles after the infusion of FVIIII, a decrease which was also observed in the study of Mobarrez et al (30). It is likely that this decrease may be related to the inclusion of these MVs in the platelet thrombus.…”
Section: Microvesiclessupporting
confidence: 88%
“…We also observed a lower number of CD62+ MVs in patients, both in the baseline sample and after the infusion of FVIII in comparison to the controls. Our patients showed a lower amount of CD144+ microvesicles after the infusion of FVIIII, a decrease which was also observed in the study of Mobarrez et al (30). It is likely that this decrease may be related to the inclusion of these MVs in the platelet thrombus.…”
Section: Microvesiclessupporting
confidence: 88%
“…One study evaluated MPs by FCM in hemophilia A patients before and after receiving FVIII infusion for a documented clinical bleeding event. The authors observed a significant decrease in total MPs, PMPs and EMPs after treatment [74]. It was suggested that MP incorporation into a developing hemostatic plug at the site of injury explained their decreasing numbers after treatment.…”
Section: Phenotypic Vs Functional Assays For Microparticle Analysismentioning
confidence: 99%
“…Notably, the detection and quantification of MVs in blood are hampered by their methods of isolation, their nanometric size, and the relatively low abundance of some specific MV subpopulations such as endothelial MVs . In this issue, Mobarrez and colleagues report on the influence of factor (F) VIII injection on MP count and activity in hemophilia A patients . The authors nicely showed that plasma MP count (except leucocyte MPs) decreased after on‐demand treatment with FVIII concentrate in hemophilia A patients and that the decrease in circulating MPs correlated with hemostatic activation.…”
Section: Proposed Guidance On the Pre‐analytical Steps For Mp Charactmentioning
confidence: 99%